Altruism and the Link to Pro-social Pandemic Behavior - Neumann-Böhme, Sebastian; Sabat, Iryna; Attema, Arthur E. (Frontiers in Health Services, 2022)
In the Corona pandemic, especially in the phase before vaccines were available, people's risk of infection with COVID-19 was dependent on the adherence to pandemic behaviours (e.g. wearing masks) of others around them. To explore whether altruistic individuals are more likely to engage in pro-social behaviours to protect others during the pandemic, we use data from the European Covid Survey (ECOS). The data was collected in September 2020 and consisted of a representative sample from seven European countries (N=7025). Altruism was measured as a deviation from purely self-interested behaviour by asking respondents how much they would be willing to donate from an unexpected gain to the equivalent of 1000€. Respondents (68.7%) who were willing to donate more than 0 Euros were treated as altruistic; on average, respondents were willing to donate 11.7% (SD 17.9) of the gain. Controlling for Country, sociodemographics, general risk aversion and COVID-specific risk aversion, we find that individuals classified as altruistic were more likely to behave prosocially. More specifically, we find that altruistic respondents were more likely to wait at home for test results and wear a mask where it is recommended. They would also stay about one day longer under quarantine without symptoms after visiting a high-risk country and were less likely to go to a supermarket with COVID symptoms. We find no significant effect for wearing a mask in places where it is mandatory and for inviting more than six people into the house. Furthermore, we find that the subjective risk assessment of COVID-19 also plays a role in these behaviours. Our results support evidence from the literature that suggests that adherence to pro-social pandemic behaviours may be increased if public health officials emphasise the altruistic nature of these behaviours.